2021
DOI: 10.1111/jir.12832
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of methylphenidate on attention deficit hyperactivity disorder in children with Down syndrome

Abstract: Background Attention deficit hyperactivity disorder (ADHD) is a common co‐morbidity that affects up to 44% of children with Down syndrome (DS). There is a need for reliable, good quality research on the use of methylphenidate within this population. The objective of this study is to report our experience regarding the management of ADHD in these children using methylphenidate. Methods This study is a retrospective observation of 21 children with DS, followed at Jérôme Lejeune Institute between 2000 and 2018. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Unfortunately, only 1 naturalistic study (n = 21) focusing on ADHD medication treatment (in this case, methylphenidate) in children with Down syndrome has been published to date. 2b This study by Roche et al, in which 48% of participants had treated congenital heart disorders, contributed the following observations: (1) The methylphenidate response rate of 76% was similar to that seen in typically developing children, (2) no serious adverse events were reported, and (3) similar to children without ID, the most commonly reported adverse events were sleep and appetite problems. Given the uncontrolled nature of the study, further study of methylphenidate effects in children with DS is certainly warranted, especially given that the limited studies of stimulant medication treatment in children with heterotypic ID have suggested that (1) rates of beneficial response may be less in children whose intelligence quotients are <50 compared with >50, and (2) there may be an increased risk of some adverse effects (e.g., social withdrawal) compared with typically developing populations.…”
Section: Tanya Froehlich MD Msmentioning
confidence: 81%
“…Unfortunately, only 1 naturalistic study (n = 21) focusing on ADHD medication treatment (in this case, methylphenidate) in children with Down syndrome has been published to date. 2b This study by Roche et al, in which 48% of participants had treated congenital heart disorders, contributed the following observations: (1) The methylphenidate response rate of 76% was similar to that seen in typically developing children, (2) no serious adverse events were reported, and (3) similar to children without ID, the most commonly reported adverse events were sleep and appetite problems. Given the uncontrolled nature of the study, further study of methylphenidate effects in children with DS is certainly warranted, especially given that the limited studies of stimulant medication treatment in children with heterotypic ID have suggested that (1) rates of beneficial response may be less in children whose intelligence quotients are <50 compared with >50, and (2) there may be an increased risk of some adverse effects (e.g., social withdrawal) compared with typically developing populations.…”
Section: Tanya Froehlich MD Msmentioning
confidence: 81%
“…While most adverse effects occur in similar proportions as in the methylphenidate clinical trial results in the United States, the proportion of gastrointestinal and neurological problems was lower than that in clinical trials [ 42 ]. A previous survey also indicated that the adverse effects of methylphenidate were different from clinical trials [ 43 ]. This may indicate that results from self-reporting, such as surveys, differ from clinical trial results.…”
Section: Discussionmentioning
confidence: 99%
“…Psychostimulants : Methylphenidate was studied in a small retrospective observational study in children with DS + ADHD and was found to be effective in 76% of cases. The most common side effects included loss of appetite and difficulty falling sleep, with 57% experiencing side effects, most which were not severe enough to interrupt treatment (Roche et al, 2021).…”
Section: Psychopharmacological Research Studies In Down Syndromementioning
confidence: 99%